Prediction of deposit oil-bearing capacity of the Tutleym series within the Krasnoleninsk arc (the Western Siberia); Bulletin of the Tomsk Polytechnic University; Vol. 310, № 1 - Abrosimova О. О. (Earth science, 2007)
Заглавие с титульного листа